Protocolo para o cuidado de enfermagem forense a mulheres em situação de violência - Almeida, Francisca das Chagas Alves de (2024)
Introduction: Violence against women stands out due to cultural, contextual, historical aspects and high incidence and prevalence rates. There are still difficulties faced by nurses in caring for women in situations of violence, with insufficient care being offered, requiring the development of protocols for the use of forensic nurses. Objective: To develop a protocol, with evidence of validity, for forensic nursing care for women in situations of violence. Method: Methodological study, developed in three stages: I) scope review; II) preparation of the care protocol; III) content validation. The analysis was carried out using the Content Validity Coefficient, Intraclass Correlation Coefficient and Appraisal of Guidelines for Research and Evaluation II. The indices considered acceptable were those equal to or greater than 0.80. The study complied with Resolution 466/2012 and Official Letter 02/2021, having been approved by the Ethics and Research Committee under CPER 30908820.90000.5188. Results: The protocol presents five approaches that must be carried out by forensic nurses when caring for women in situations of violence: prevention of violence; identification of violence, interventions, referrals and monitoring of women in situations of violence, in addition to limitations to care related to organizational problems, professional and individual issues of women. The content of this protocol was evaluated based on the six domains and 23 items of the Appraisal of Guidelines for Research and Evaluation II: scope and purpose, involvement of the parties, rigor of development, clarity of presentation, applicability, independence, and overall quality of the instrument and recommendation of its use. The data reveal that a content validity coefficient of 0.97 was obtained, an intraclass correlation coefficient greater than 0.87 and the Appraisal of Guidelines for Research and Evaluation II 0.94. Conclusion: The protocol presents evidence of validity, and its use is recommended by forensic nurses, as it is applicable to their practice and can contribute to care management, reformulation and construction of new policies and guidelines that guide managers and nurses with regard to forensic care provided to women in situations of violence, awareness raising in training processes and research into more inclusive approaches and tackling the phenomenon of violence.